Multisystemic therapy versus management as usual in the treatment of adolescent antisocial behaviour (START): 5-year follow-up of a pragmatic, randomised, controlled, superiority trial. (May 2020) - Fonagy, Peter; Butler, Stephen; Cottrell, David; Scott, Stephen; Pilling, Stephen; Eisler, Ivan; Fuggle, Peter; Kraam, Abdullah; Byford, Sarah; Wason, James; Smith, Jonathan A; Anokhina, Alisa; et al.
Summary: Background: Multisystemic therapy is a manualised treatment programme for young people aged 11–17 years who exhibit antisocial behaviour. To our knowledge, the Systemic Therapy for At Risk Teens (START) trial is the first large-scale randomised controlled trial of multisystemic therapy in the UK. Previous findings reported to 18 months after baseline (START-I study) did not indicate superiority of multisystemic therapy compared with management as usual. Here, we report outcomes of the trial to 60 months (START-II study). Methods: In this pragmatic, randomised, controlled, superiority trial, young people (aged 11–17 years) with moderate-to-severe antisocial behaviour were recruited from social services, youth offending teams, schools, child and adolescent mental health services, and voluntary services across England, UK. Participants were eligible if they had at least three severity criteria indicating past difficulties across several settings and one of five general inclusion criteria for antisocial behaviour. Eligible families were randomly assigned (1:1), using stochastic minimisation and stratifying for treatment centre, sex, age at enrolment, and age at onset of antisocial behaviour, to management as usual or 3–5 months of multisystemic therapy followed by management as usual. Research assistants and investigators were masked to treatment allocation; the participants could not be masked. For this extension study, the primary outcome was the proportion of participants with offences with convictions in each group at 60 months after randomisation. This study is registered with ISRCTN, ISRCTN77132214, and is closed to accrual. Findings: Between Feb 4, 2010, and Sept 1, 2012, 1076 young people and families were assessed for eligibility and 684 were randomly assigned to management as usual (n=342) or multisystemic therapy (n=342). By 60 months' of follow-up, 188 (55%) of 342 people in the multisystemic therapy group had at least one offence with a criminal conviction, compared with 180 (53%) of 341 in the management-as-usual group (odds ratio 1·13, 95% CI 0·82–1·56; p=0·44). Interpretation: The results of the 5-year follow-up show no evidence of longer-term superiority for multisystemic therapy compared with management as usual. Funding: National Institute for Health Research Health Services and Delivery Research programme.